Beginning Visual C♯ 2012 programming - Watson, Karli (Wrox beginning guides., 2013)
Step-by-step beginner's guide to Visual C♯ 2012 Written for novice programmers who want to learn programming with C♯ and the .NET framework, this book offers programming basics such as variables, flow control, and object oriented programming. It then moves into web and Windows programming and data access (databases and XML). The authors focus on the tool that beginners use most often to program C♯, the Visual C♯ 2012 development environment in Visual Studio 2012. Puts the spotlight on key beginning level topics with easy-to-follow instructions for Microsoft Visual C♯ 2012.